Imaging 2D Breast Cancer Tumor Margin at Terahertz Frequency using Numerical Field Data based on DDSCAT - Bowman, T. C.; Hassan, A. M.; El-Shenawee, M. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
This work presents tomography of breast cancer tumor margins in the terahertz frequency band. The discrete dipole approximation is employed to calculate the electromagnetic fields scattered from simulated heterogeneous breast tumors. Two-dimensional Comedo with necrotic core and papillary breast tumor patterns are computer-generated for this investigation. The Rytov approximation is applied to terahertz scattered field data calculated at a line of receivers in the far field from the samples. The obtained tomography images demonstrate a potential for terahertz frequency for identifying and assessment of breast cancer tumor margins.